Relationship between Knowledge, Intentions, and Anaemia Prevention Behavior on Common Symptoms of Anaemia in Adolescent Girls in Rural Areas Indonesia - Muhammad Rachmat; Citrakesumasari; Sitti Andriani Anwar; Yessy Kurniati; Nasrah (International Journal of Advanced Health Science and Technology, 2024)
Anaemia is a prevalent nutritional issue that disproportionately affects teenage girls in Indonesia, particularly those residing in rural regions. A research study found that 23.4% of adolescent ladies suffer from anaemia. Furthermore, individuals residing in rural regions exhibit a heightened susceptibility to anaemia, which is twofold in comparison to their urban counterparts. This study employs a cross-sectional design. The questionnaire is designed to assess the participants' understanding of the elements that contribute to anaemia and their viewpoints on anaemia. It was handed out to a total of 242 participants from various schools in Gowa, South Sulawesi. Out of the students who have mostly good goals, 41.3% can correctly identify their menstrual cycle with a significant level of p=0.001. On the other hand, their understanding of their menstrual cycle is mostly limited. The student had pallor in their face, eyelids, lips, skin, nails, and palms over a prolonged period, as evidenced by the intention and behaviour variable with a p-value of less than 0.05. Nevertheless, the data also reveals a minimal incidence of students who continuously exhibit pallor during their menstrual cycle. In contrast, most pupils in the "never" category exhibit a pallid complexion. The current study's poor comprehension of adolescent anaemia highlights the need for further investigation by educational institutions and governmental authorities. This should include a research of the factors that drive adolescent girls to recognise the symptoms of anaemia.